Subensemble concept in 2D magnetized particle transport model - Zasenko, V.I.; Cherniak, O.M.; Zagorodny, A.G. (Вопросы атомной науки и техники, 2016)
Transport of magnetized particle undergoing random frozen isotropic electrostatic field is considered. Because of infinitely long field correlation time and particle trapping this problem is of particular interest as a test for closure of statistical equations. The concept of subensembles is incorporated here in the analytical approach we developed earlier. The Lagrangian velocity correlation function is calculated in the drift approximation. To verify validity of the analytical method the results are compared with ones found from a direct numerical simulation. А better quantitative agreement obtained with the use of subensemble concept is shown.